(3QSGdI aj BOGH GdHMKs - (3GdEjLj, CHh GdaVd, YVO GdOjf, YHO GdQMef Hf CMeO Hf YHO GdZaGQ, J (B756(3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3gPg QSGdI aj BOGH GdHMK jMJGL EdjgG cd eJYde dJchf MGaXI dg aj GdHMK ef GdVdGd hJSgd Ydjg WQjb Gdage hGdJagje hEf gj hEf cGfJ eJOGhdI Hjf GdeMbbjf dcfgG eG cGfJ efXheI aj Sdc (B...s
(3BNQgG (B:s
... (3cPdc Ydi JbOjQ YOe Ydjg Tehd GdhdGjI HLhGR Cf jchf Pdc GdJbOjQ eMGdG hGdeMGd LGR Cf jSJdRe GdeMGd afbhd gPG GdefY dG jVQfG dCfg dh cGf Pdc GdJbOjQ KGHJG aj faS GdCeQ (B.. (3Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\295s
(3cTa GdXfhf (B1\41s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs